Induction of Angiogenesis by a Type III Phosphodiesterase Inhibitor, Cilostazol, Through Activation of Peroxisome Proliferator-Activated Receptor-γ and cAMP Pathways in Vascular Cells - Sanada, Fumihiro; Kanbara, Yasuhiro; Taniyama, Yoshiaki; Otsu, Rei; Carracedo, Miguel; Ikeda-Iwabu, Yuka; Muratsu, Jun; Sugimoto, Ken; Yamamoto, Koichi; Rakugi, Hiromi; Morishita, Ryuichi (Arteriosclerosis, thrombosis, and vascular biology, 2016)
OBJECTIVE—Peripheral arterial disease is highly prevalent in the elderly and in the subjects with cardiovascular risk factors such as diabetes. Approximately 2% to 4% of those affected with peripheral arterial disease commonly complain of intermittent claudication. Cilostazol, a type III phosphodiesterase inhibitor, is the only Food and Drug Administration–approved drug for the treatment of intermittent claudication. Cilostazol has been shown to be beneficial for the improvement of pain-free walking distance in patients with intermittent claudication in a series of randomized clinical trials. However, the underlying mechanism how cilostazol improved intermittent claudication symptoms is still unclear. APPROACH AND RESULTS—In this study, the effect of cilostazol on ischemic leg was investigated in mouse ischemic hindlimb model. Administration of cilostazol significantly increased the expression of hepatocyte growth factor (HGF), vascular endothelial growth factor, angiopoietin-1, and peroxisome proliferator-activated receptor-γ in vasculature. The capillary density in ischemic leg was also significantly increased in cilostazol treatment group when compared with control and aspirin treatment group. However, an increase in capillary density and the expression of growth factors was almost completely abolished by coadministration of HGF-neutralizing antibody, suggesting that cilostazol enhanced angiogenesis mainly through HGF. In vitro experiment revealed that cilostazol treatment increased HGF production in vascular smooth muscle cells via 2 major pathwaysperoxisome proliferator-activated receptor-γ and cAMP pathways. CONCLUSIONS—Our data suggest that the favorable effects of cilostazol on ischemic leg might be through the angiogenesis through the induction of HGF via peroxisome proliferator-activated receptor-γ and cAMP pathways.